2017
DOI: 10.1177/1362361317726417
|View full text |Cite
|
Sign up to set email alerts
|

Associations between cooperation, reactive aggression and social impairments among boys with autism spectrum disorder

Abstract: Cooperation is a fundamental human ability that seems to be inversely related to aggressive behaviour in typical development. However, there is no knowledge whether similar association holds for children with autism spectrum disorder. A total of 27 boys with autism spectrum disorder and their gender, age and total score intelligence matched controls were studied in order to determine associations between cooperation, reactive aggression and autism spectrum disorder-related social impairments. The participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 73 publications
(122 reference statements)
0
3
0
1
Order By: Relevance
“…Deficits in these higher cognitive functions, particularly, empathy, are likely to lead to abnormalities in complex social behaviors, such as social competition and cooperation [ 6 , 7 ]. Indeed, major symptoms of high-functioning autism include empathic incapacity, reactive aggression and impaired complex social behaviors [ 8 , 9 ]. However, whether these behavioral features are recapitulated in ASD model animals has received limited research attention.…”
Section: Introductionmentioning
confidence: 99%
“…Deficits in these higher cognitive functions, particularly, empathy, are likely to lead to abnormalities in complex social behaviors, such as social competition and cooperation [ 6 , 7 ]. Indeed, major symptoms of high-functioning autism include empathic incapacity, reactive aggression and impaired complex social behaviors [ 8 , 9 ]. However, whether these behavioral features are recapitulated in ASD model animals has received limited research attention.…”
Section: Introductionmentioning
confidence: 99%
“…The task represents the conflict between the optimum distribution of rewards (Pareto optimal) and the optimum choice for an individual (Nash equilibrium) ( Apt & Grädel, 2011 ) It is considered an analogue of social interaction and as such it has been used a lot in autism research where social behaviour and interactions are key characteristics of the disorder. Findings concerning the PD task in autism, indicate that, cooperation could improves with age ( Jin et al, 2020 ; Kaartinen et al, 2019 ) and the development of executive functions ( Li, Zhu & Gummerum, 2014 ) and that reputation ( Maurer et al, 2018 ) and the nature of the opponent (actual human or machine) could also influence cooperation. These factors are important for both autistic ( Sally & Hill, 2006 ) and non autistic individuals ( Mienaltowski & Wichman, 2020 ; Milinski & Wedekind, 1998 ; Wang et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, published studies on the neuropsychological functioning of ASD show contrasting results due to methods issued without providing exhaustive answers in explaining the neuropsychological dysfunctions in the ASD population. Studies on social decision-making as cooperation indicated lower correct predictions of others' moves compared with TDCs (81) and an improvement of this ability with age (82,83). Moreover, for individuals with ASD, their cooperation relies on more rigid criteria that does not differ depending on the morality of the interacting partner (84).…”
Section: Discussion and Clinical Implicationsmentioning
confidence: 99%